Pengaruh Product Quality Dan Brand Love Terhadap Repurchase Intention Pada Brand Apple - Giovandhi, Leonardo; Adlina, Hafiza (Jurnal Ilmiah Wahana Pendidikan, 2024)
Along with the times, the higher the technology used. Smartphones and laptops are becoming increasingly common for people today. Apple is one of the multinational companies that developed these technologies. Apple products have been widely used in Indonesia because of the good quality of its products with a good brand name. Apple always maintains the quality of the products it releases, but several factors make Apple unable to maintain its sales level. This study aims to analyze the effect of product quality and brand love on the repurchase intention of the Apple brand in Medan City. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out through probability sampling techniques and used 100 respondents as samples. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analyses, partial tests, simultaneous tests, and coefficient of determination tests. The results of this study indicate that the variables of product quality and brand love have a positive and significant effect both partially and simultaneously on repurchase intention, and have an effect of 86.8%, while the remaining 13.2% is influenced by other factors outside this research model.